Minimizing Time and Cost in The Iraqi AEC industry by Adopting Building Information Modeling (BIM) Technique. - Mahmood Maad Mahdi; Khalil Ismail Wali; Burog Abdullhalim Yuosif (Zanco Journal of Pure and Applied Sciences, 2020)
The Architectural, Engineering, and Construction (AEC) industry is essential for its direct influence on the development of any country, particularly in terms of economy. Thus, problems related to cost and time arise as a global phenomenon in this industry, particularly in the third world countries like Iraq. The Building information modeling (BIM) technique is considered as the most adequate technique that overcomes the problems facing the AEC industry. This paper aimed to assess the causes of cost issues and time delays in the Iraqi AEC industry and to outline the BIM concept and the benefits of its application for solving these problems. This paper consists of two parts; the first one is the quantitative approach, which was adopted for data collection through a specially designed questionnaire form; these questionnaires were spread among 50 of the top and middle management in different construction companies, and other experts in the arena of AEC industry. The results of the statistical analysis showed that the highest influential factors on cost and time overrun are: inadequate planning and scheduling, selecting inefficient contractors, change orders, and the errors and mistakes in preparing the bill of quantities and materials (BOQ/BOM) with relative importance index (RII) of 0.98, 0.87, 0.83 and 0.82 respectively. The second part of this paper reviewed the benefits of applying BIM and highly recommend this technology to improve the local AEC industry. The application of the BIM technique will lead to more sustainable design, construction, and project delivery in the Iraqi projects. This paper presents a significant set of recommendations that demonstrate how BIM technique can be applied to overcome the challenges of the AEC industry in Iraq. It unlocks the door for further authentic researches on the adoption of BIM technique as an influential and exceptional tool to point out the issues related to time and cost in the AEC industry in Iraq.